Java source code development toolkit for multimedia - Chua, Agnes Yu Fern (Universiti Malaysia Sarawak (UNIMAS), 2005)
Java is one of the most important programming languages. The Java Source Code Development Toolkit aims to provide a toolkit that will act as guideline on writing Java Source Codes. The prototyped system will include three important topics, naming Class & Inheritance, Graphical User Interface (GUI) and Multimedia (MM). The prototyped system contains the interesting features of each topic. The components under Class & Inheritance are super class and Inheritance. Meanwhile, in GUI there are button, label, checkbox, combobox, radiobutton and text area. Moreover, interesting features ion MM such as images, animation and audio are included in the prototyped system as well. For further work, this project can be enhanced and extended to more attractive toolkit.